Supramolecular chemistry at the liquid/solid interface probed by scanning tunnelling microscopy. (23rd October 2006) - De Feyter, S.; Uji-i, H.; Mamdouh, W.; Miura, A.; Zhang, J.; Jonkheijm, P.; Schenning, A.P.H.J.; Meijer, E.W.; Chen, Z.; Wurthner, F.; Schuurmans, N.; Esch, J.; et al.
The liquid/solid interface provides an ideal environment to investigate self-assembly phenomena, and scanning tunnelling microscopy (STM) is one of the preferred methodologies to probe the structure and the properties of physisorbed monolayers on the nanoscale. Physisorbed monolayers are of relevance in areas such as lubrication, patterning of surfaces on the nanoscale, and thin film based organic electronic devices, to name a few. It is important to gain insight in the factors which control the ordering of molecules at the liquid/solid interface in view of the targeted properties. STM provides detailed insight into the importance of molecule-substrate (epitaxy) and molecule-molecule interactions to direct the ordering of both achiral and chiral molecules on the atomically flat surface. The electronic properties of the self-assembled physisorbed molecules can be probed by taking advantage of the operation principle of STM, revealing spatially resolved intramolecular differences within these physisorbed molecules.